PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN UPT CREW KA SURABAYA KOTA PT. KAI DAOP VIII MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING - Mohamad Tambrin; Bambang Sudarsono; Dwi Ayuningsih (Eco-Entrepreneur, 2018)
ABSTACTThe aims of this study are (1) to analyze whether organizational commitment has a positive and significant effect on employee performance, (2) to analyze whether organizational commitment has a positive and signicant effect on motivation, (3) to analyze whether motivation has a positive and significant effect on employee performance,(4) to analyze whether organizational commitment has a positive and significant effect employee performance with motivation as intervening variable. This study uses quantitative method that population is all of employee in UPT CREW KA Surabaya- Kota PT KAI DAOP VIII which amounts to 189 employee. Using the Simple Random Sampling is got 129 employee as responden. The hypothesis of this study are: (1) organizational commitment has a positive and significant effect on employee performance; (2) organizational commitment has apositive and signicant effect on motivation;(3) motivation has a positive and significant effect on employee performance;(4) organizational commitment has a positive and significant effect employee performance with motivation as intervening variable. Based on path analysis, the result showed that; (1) organizational commitment has a positive and significant effect on employee performance with value 38,5% (2) organizational commitment has a positive and signicant effect on motivation with value 78,7% (3) motivation has a positive and significant effect on employee performance with value 49% (4) organizational commitment has a positive and significant effect employee performance with motivation as intervening variable with value 38,6%.